BUILDING USER TRUST IN RURAL MOBILE BANKING THROUGH ISLAMIC MARKETING: THE ROLES OF FINANCIAL EDUCATION, ASSISTANCE, AND RISK AWARENESS - Adzan Noor Bakri; Mursyid; Azizah Samsir (Academic Bright Collaboration, 2026)
This study examines how financial education and assistance shape trust in technology, perceived technology risk, and user trust in mobile banking among rural Muslim users. It uses Islamic marketing as an interpretive framework to explain digital trust in a rural context where mobile banking access has expanded faster than users’ financial and digital literacy. A quantitative cross-sectional survey was conducted among 110 rural mobile banking users in Wasuponda Village, Wasuponda District, East Luwu. Data were collected using a five-point Likert-scale questionnaire and analyzed with PLS-SEM using SmartPLS 4. The measurement model was assessed through outer loadings, CR, AVE, and HTMT, while the structural model was evaluated using bootstrapping, confidence intervals, R², f², VIF, blindfolding, and PLSpredict. The measurement model met acceptable reliability and validity criteria. The structural model was only partially supported. Financial education significantly increased user trust (β = 0.674; p < 0.001) and perceived technology risk (β = 0.373; p = 0.013). Other paths, including assistance, trust in technology, and perceived technology risk toward user trust, were not significant. The model explained 59.8% of user trust, with no serious collinearity problems. Financial education was the most consistent pathway in this model for strengthening informed trust. However, the findings are limited by the cross-sectional design, single rural setting, purposive sampling, and self-reported data. The study identifies a two-track education effect: financial education increases both user trust and risk awareness. Islamic marketing values are used as an interpretive lens, not as directly measured variables.